Darier’s disease: a new paradigm for genetic studies in psychiatric disorders - Cordeiro Júnior, Quirino; Werebe, Daniela Meshulam; Vallada, Homero (São Paulo Medical Journal, 2000)
CONTEXT: One strategy for identifying susceptibility genes for common disorders is to investigate Mendelian diseases, cosegregating with these common disease phenotypes. CASE REPORT: A family with seven members is described, in which three members present Darier’s disease and depression. This apparent cosegregation, if true, would support the hypothesis that in some pedigrees, a gene for mood disorder may be located on chromosome 12.